67.2k views
0 votes
The graph of function f is shown on the coordinate plane. Graph the line representing function g, if g is defined as shown below.

G(x)=1/2f(x+2)

The graph of function f is shown on the coordinate plane. Graph the line representing-example-1

2 Answers

1 vote

Answer:


g(x)=x-1

Explanation:

Any problem of this kind should first be approached by solving the initial function.

This question is based on curve translation on x-axis. But, there can be questions asked on translation in both axes, rotation of curve about origin, or both combined.

Initial function f(x) is a straight line from picture.

Common equation of straight line is


y=mx+c

m= slope of the line

c= y-intercept

Slope of the line:


m=(y_(2)-y_(1) )/(x_(2)-x_(1))

Let those points on graph be A(3,0) and B(0,-6)

Therefore, slope of line AB, using formula is:


m=(0-(-6))/(3-0)

m=2

And c=(-6)

And equation of line AB is:


y=2x-6


f(x)=2x-6

Now this line is translated backwards by 2 units, (x) becomes (x+2)

Let us consider a X, such that,
X=x+2


f(X)=2X-6


f(x+2)=2(x+2)-6


f(x+2)=2x+4-6


f(x+2)=2x-2

Now, there is another function such that,
g(x)= (1)/(2) f(x+2)


g(x)= (1)/(2)(2x-2)


g(x)= x-1 ; according to your question.

In the picture, they are asking for a function,
g(x)= (-1)/(2) f(x+2)

Then,
g(x)= -x+1 ; according to the picture.

Here, I have attached a file showing all the graphs for clear understanding.

The graph of function f is shown on the coordinate plane. Graph the line representing-example-1
User Vadimvolk
by
5.8k points
3 votes

Answer:

See attachment below.

Explanation:

f is a first-order polynomial, whose form is:


y = m\cdot x + b

Where:


x - Independent variable.


y - Dependent variable.


m - Slope.


b - y-Intercept.

The y-Intercept is equal to the value of the dependent variable when the independent variable is zero. Then:


b = -6

The slope is the ratio of the change in the dependent variable to the change in the independent variable. Hence:


m =(\Delta y)/(\Delta x)


m = (0-(-3))/(3-0)


m = 1

The equation for f is:


f(x) = x -6

The expression for g is found after substituting into and manipulating f:


g(x) = -(1)/(2)\cdot [(x+2)-6]


g(x) = -(1)/(2)\cdot (x-4)


g(x) = -(1)/(2)\cdot x + 2

The graph of the new function is plotted herein.

The graph of function f is shown on the coordinate plane. Graph the line representing-example-1
User Mkopala
by
5.6k points